Troubleshooting your web page - Callahan, Evan (Microsoft P. RedmondUS, 2001)
Provides illustrated guidelines for troubleshooting in areas including: animataion, backgrounds, borders, browsers, colour, databases, FrontPage 2000, images, layout, multimedia, and text formatting. Covers web browsers: Microsoft Internet Explorer and Netscape; web authorizing tools such as: Microsoft FrontPage and Allaire HomeSite; and graphics programs including Adobe Photoshop and Macromedia Fireworks.